Emerging MXene@Metal-Organic Framework Hybrids: Design Strategies toward Versatile Applications - Saini, Haneesh; Srinivasan, Nikitha; Šedajová, Veronika; Majumder, Mandira; Dubal, Deepak P; Otyepka, Michal; Zbořil, Radek; Kurra, Narendra; Fischer, Roland A; Jayaramulu, Kolleboyina (ACS nano, 2021)
Rapid progress on developing smart materials and design of hybrids is motivated by pressing challenges associated with energy crisis and environmental remediation. While emergence of versatile classes of nanomaterials has been fascinating, the real excitement lies in the design of hybrid materials with tunable properties. Metal-organic frameworks (MOFs) are the key materials for gas sorption and electrochemical applications, but their sustainability is challenged by limited chemical stability, poor electrical conductivity, and intricate, inaccessible pores. Despite tremendous efforts towards improving the stability of MOF materials, little progress has made researchers inclined toward developing hybrid materials. MXenes, a family of two-dimensional transition-metal carbides, nitrides and carbonitrides, are known for their compositional versatility and formation of a range of structures with rich surface chemistry. Hybridization of MOFs with functional layered MXene materials may be beneficial if the host structure provides appropriate interactions for stabilizing and improving the desired properties. Recent efforts have focused on integrating Ti3C2Tx and V2CTx MXenes with MOFs to result in hybrid materials with augmented electrochemical and physicochemical properties, widening the scope for emerging applications. This review discusses the potential design strategies of MXene@MOF hybrids, attributes of tunable properties in the resulting hybrids, and their applications in water treatment, sensing, electrochemical energy storage, smart textiles, and electrocatalysis. Comprehensive discussions on the recent efforts on rapidly evolving MXene@MOF materials for various applications and potential future directions are highlighted.
Keywords: smart textiles; derivatives; metal−organic frameworks; energy storage; catalysis; metal−sulfur batteries; Ti3C2Tx MXene; hybrids; environmental remediation